Mechanical properties and microstructure of cement mortars incorporating Cd-zeolitized fly ash - Monzón, Jorge Daniel (2018)
A solid enriched with NaA zeolite was synthesized from a coal fly ash, and the so-obtained zeolitized material was used as ion exchanger for purifying aqueous solution containing cadmium cations. Mechanical strengths and drying shrinkage measured on cement mortars containing not more than 10 wt% of the zeolitized product showed that the cement properties remained unaltered, being similar to those corresponding to mortars where non-zeolitized starting fly ash was used in the mortar formulation. SEM analyses of fractured mortars show zeolitized fly ash particles strongly anchored inside the microstructure, the particle surfaces being densely covered by hydration products. To analyze the viability of final disposal for the cadmium sludge obtained after ion exchange, a leaching test was performed on cement pastes containing 10 wt% of cadmium-exchanged zeolite (Cd-ZFA10) showing that the present methodology is an effective procedure for the immobilization of the heavy metal.